Genetic basis of minicell formation in Escherichia coli K-12. - Davie, E (1984)
Hfr- and P1-mediated genetic transfer experiments failed to confirm the presence of a " minA " gene in Escherichia coli K-12, leading to the conclusion that mutation at a single locus, the minB locus, is sufficient to cause minicell production in this species.